Flying to the Moon and other strange places - Collins, Michael, 1930-2021 (Farrar, Straus and Giroux, 1976)
The author, an astronaut, discusses his early career, his training for space flight, his trips into space including the first lunar landing, and the possibilities for life and flight in space in the future.